POLICY OF REGIONAL GOVERNMENT OF MAGELANG REGENCY ON FOREIGN INVESTMENT OF TOURISM - Febri Rizki Kurniawan; Dyah Adriantini Sintha Dewi; Bambang Tjatur Iswanto (Universitas Negeri Semarang, 2019)
Tourism is one of the sources of Original Regional Revenue that is quite promising, when it is managed professionally. With regard to funds, the presence of foreign investment is a very possible solution. From the collected data, in the Regency of Magelang, the presence of foreign investors in tourism is still very little, while such potential is wide open for development. For this reason, this research is entitled